Changes in R 3.6-4.0 - Kalibera, Tomas; Meyer, Sebastian; Hornik, Kurt (The R Journal, 2020)
We give a selection of the most important changes in R 4.0.0 and in the R 3.6 release series. Some statistics on source code commits and bug tracking activities are also provided.
CRIS-Team WoS Importer:2021-03-05